Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.4312
|View full text |Cite
|
Sign up to set email alerts
|

THU0626 Cost-effectiveness of early treatment of acpa positive rheumatoid arthritis patients with abatacept

Abstract: BackgroundStudies have reported that the presence of elevated anti-citrullinated protein antibodies (ACPA)/RF levels, together with joint erosions, is associated with higher disease burden in terms of disability, and mortality in rheumatoid arthritis (RA). Abatacept has been shown to be effective in this patient population with favorable comparative data against adalimumab.(1) However, few studies have investigated the cost effectiveness of abatacept in this population to similar treatments such as TNFs.Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The findings from our analysis are consistent with such a model in which an early 'window of opportunity' exists to achieve the best outcomes. Moreover, the use of abatacept as a first-line bDMARD following an inadequate response to MTX has been shown to be more cost-effective than the use of adalimumab at this stage, in anti-citrullinated protein antibody-positive patients with RA [9].…”
mentioning
confidence: 99%
“…The findings from our analysis are consistent with such a model in which an early 'window of opportunity' exists to achieve the best outcomes. Moreover, the use of abatacept as a first-line bDMARD following an inadequate response to MTX has been shown to be more cost-effective than the use of adalimumab at this stage, in anti-citrullinated protein antibody-positive patients with RA [9].…”
mentioning
confidence: 99%
“…Therefore, they found that 99mTc-3PRGD2 is a promising agent for the early diagnosis of rheumatoid arthritis. The study was conducted in Germany [4] . The results of the study suggests that an early treatment of patients with abatacept has advantages compared to adalimumab for both the patients and the payers and treatment with abatacept appears to have lower costs per response (remission) compared to treatment with adalimumab as a first bDMARD.…”
Section: Resultsmentioning
confidence: 99%
“…This study included costs for drugs, concomitant drugs, disease monitoring, and adverse events. Another study developed a decision tree model to compare the cost-effectiveness of abatacept to adalimumab over 2 years in Germany among the same target population as the previous cost per responder/remission study 34 . The model allowed switching to second-line and third-line of biologic therapy for patients who do not respond to the first line abatacept or adalimumab.…”
Section: Discussionmentioning
confidence: 99%